(untitled) (Biocenosis, 2012)
The results gathered from the pre test Perception of the Environmental Dimension, applied in the course Environmental Dimension in the university work, and taught by Interuniversity Commission for Environmental Education (CIEA-CONARE)are shown in this study. Three Costa Rican public universities including the Universidad Nacional (UNA), the Universidad Estatal a Distancia (UNED), and the Universidad de Costa Rica (UCR) at UNA’s Liberia campus housed professors, students, administrative personnel, and others who received this course from August 5th to September 9th 2011. The instruments consist of Environmental Dimension indicators designed to register and monitor the processes of this test. Since the results shown in this study are preliminary, it was possible to validate the function of the instrument through a pilot test and to detect the students’ perception of Environmental Dimension at the beginning of the course. The indicators analyzed involved aspects related to the participant’s personal and labor life.